Game theoretic analysis of congestion, safety and security traffic and transportation theory - Hausken, Kjell; Zhuang, Jun; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
Maximizing reader insights into the interactions between game theory, excessive crowding and safety and security elements in traffic and transportation theory, this book establishes a new research angle by illustrating linkages between different research approaches and through laying the foundations for subsequent analysis. Congestion (excessive crowding) is defined in this work as all kinds of flows; e.g., road/sea/air traffic, people, data, information, water, electricity, and organisms. Analyzing systems where congestion occurs ? which may be in parallel, series, interlinked, or interdependent, with flows one way or both ways ? this book puts forward new congestion models, breaking new ground by introducing game theory and safety/security. Addressing the multiple actors who may hold different concerns regarding system reliability; e.g. one or several terrorists, a government, various local or regional government agencies, or others with stakes for or against system reliability, this book describes how governments authorities, and others may have the tools to handle congestion, but that these tools need to be improved whilst additionally ensuring safety and security against various threats. This game-theoretic analysis sets this book apart from the current congestion literature and ensures that the book will be of use to postgraduates, researchers, 3rd/4th-year undergraduates, policy makers, and practitioners.
Electronic reproduction.
Keywords: Game theory; Traffic congestion -- Mathematical models; Traffic flow -- Mathematical models; Electronic books